The development and evaluation of a programme to promote sensitive pscyhotherapeutic practice with gay men and lesbians - Coetzee, Catherine Ann (Rhodes University, Faculty of Humanities, Department of Psychology, 2009)
Clinical psychology's relevance and future viability depend on its ability to render services that are relevant and sensitive to multicultural and minority issues. Lesbian, gay, bisexual and transgendered people are one such group that professional psychology "“ both in South Africa and abroad - has identified as having unique treatment needs for which psychologists require specialised knowledge and skills in order to render appropriate treatment. Competence to treat non-heterosexual patients has been framed in terms of a gay affirmative paradigm which has as its basic tenet the recognition that same-gender orientation is not pathological but rather a healthy alternative to heterosexuality. From this perspective being "gay friendly" or "gay accepting" is not enough. To implement a gay affirmative approach in practice, practitioners must have resolved their possible prejudice and heterosexist bias and have the requisite knowledge of concerns unique to lesbian, gay, and bisexual (LGB) individuals to be able to apply their skills in a culturally sensitive manner. Although more American post-graduate psychology programmes are addressing sexual diversity, their failure to produce psychologists who feel competent to treat lesbian/gay or bisexual individuals has highlighted the need to develop effective training strategies based on empirical nvestigation. The dearth of comparable data about local South African psychology training prompted this inquiry which had four broad aims namely, (i) to establish to what extent trainees' prior training had equipped them with the knowledge, awareness, and skills to approach their work with non-heterosexual patients in a gay affirmative manner, and (ii) to implement and (iii) to evaluate to what extent a brief structured training programme is effective in engaging the trainees; in increasing knowledge, in raising awareness, and in changing specific attitudes and imparting specific skills required for treating lesbian and gay patients.; and (iv) what, if any, recommendations should be made for the future with respect to training of sychologists in this area? The field of sexual orientation research has been expanded to include issues pertaining to bisexual, transgendered and intersexed people, but serious time constraints meant that issues pertaining to these groups could not be addressed in depth. Although the exclusion of these groups is problematic and may be seen as reinforcing their invisibility, it was decided to focus primarily on gay and lesbian issues s an introduction to same-sex orientation. It is envisaged that bisexual and transgender issues would be dealt with in depth in more advanced training. Nine trainee psychologists employed at hospitals in the greater Cape Town area volunteered to participate in the programme which comprised a series of two-hour experiential workshops offered once a week over six weeks. The study employed both quantitative and qualitative data analysis methods. The first stage entailed gathering information to better understand trainees' existing level of competence. Individual interviews were conducted prior to the course to obtain data about their attitudes and perceptions regarding the need for such specialised training, and how qualified they considered themselves to be to treat LGB patients, and their experience in this regard. For the purpose of the over-all analysis information was also gathered about pertinent personal and social characteristics of the trainees, as well as their contact with lesbian/gay persons. In addition, an attitude survey and the Lesbian, Gay, and Bisexual Counselling Self-efficacy Scale (LGB-CSI) were administered to obtain benchmarks against which change could be measured. The second stage involved the implementation of the educational programme and gathering information about trainees' responses to its various components. This stage concentrated on discovering how individual trainees reacted to material on lesbian, gay, and bisexual issues and how they used the programme to improve their self-awareness and skills. The results indicate that local psychology training might not address same-gender orientation adequately, thus reinforcing trainees' belief that sexual orientation is irrelevant, and that their generalist training equips them to work with gay/lesbian/bisexual patients. While the training strengthened existing positive attitudes, it was less effective in changing blatant antigay prejudice. However, both quantitative and qualitative data suggest that the programme increased individuals' awareness and insight into their previously unrecognised heterosexist biases and created greater understanding of the effects of stigmatisation on sexual minority individuals. In addition, the training increased trainee's sense of competence to provide affirmative treatment as evidenced by the significant differences between the pre- and post-training mean scores on the Relationship, Knowledge, and Advocacy Scales and between the mid- and post-training means scores on the Assessment and Awareness Scales of the LGB-CSI. Despite the limited generalisability of these findings on account of possible sampling bias, the need and value of such training was confirmed by trainees' recommendation that this programme should be a mandatory offering in the first year of clinical psychology training.
Keywords: Psychotherapy -- Practice -- South Africa; Psychoanalysis and homosexuality -- South Africa; Homosexuality -- Social aspects -- South Africa; Homosexuality -- Psychological aspects -- South Africa; Psychotherapy -- Moral and ethical aspects -- South Africa; Psychologists -- Training of -- South Africa